Comprehensive natural resources evaluation from multi-category aggregation: a case study of Huanggang - Xuebo Weng; Xianbin Shi; Xiaoning Zhou; Shuai Leng; Jingmeng Huang; Shaonan Peng (All Earth)
Despite China’s efforts to conduct unified investigations and monitoring, gaps remain in the comprehensive evaluation of natural resources. A major challenge is the aggregation of data from different categories at the county level, which is crucial for sustainable development. We collected data for Huanggang City, China, for the years 2020–2022, converted them into plane data, and applied multi-criteria decision analysis to examine the natural resource characteristics of Huanggang, which has 10 county-level administrative regions. An evaluation system comprising 56 indices for land, water, forest, wetlands, and minerals was constructed. The analytic hierarchy process and ordered weighted averaging were used for single-resource categories, while the entropy weight method and technique for order preference by similarity to the ideal solution were used to aggregate multi-resource categories. The southern alluvial plain of Huanggang is a favourable location for mineral and land development, whereas northern mountainous and hilly areas are well suited for the growth of green ecological industries focused on water, forest, and wetland ecological functions. The results of this study provide guidance for resource development policies at the county-level, offer a reference for enhancing resource development and protection, and support the Sustainable Development Goals.